Cassava and sweetpotato cropping practices and farmer communication networks in Quan Binh Province, Vietnam. - Wilkins, K. (2017)
Recognizing the potential of RTCs in increasing the resilience of smallholder farmers against climate change impacts in Vietnam, this research was done with the goal of determining potential gaps in farmer knowledge about climate smart practices for cassava and sweetpotato production. It also aimed to characterize farmer communication networks and knowledge-sharing within the village as well as at the commune-level.